2018
DOI: 10.1021/acs.est.8b01540
|View full text |Cite
|
Sign up to set email alerts
|

Human Sex Hormone Disrupting Effects of New Flame Retardants and Their Interactions with Polychlorinated Biphenyls, Polybrominated Diphenyl Ethers, a Case Study in South China

Abstract: Even though sex hormone disrupting effects of polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) are widely understood, similar effects associated with new flame retardants (NFRs) have not been so well studied. This study aimed to explore the sex hormone disruption of NFRs and their interactions with PCBs and PBDEs through the conduct of an ecological study in an e-waste dismantling and control region in South China. Questionnaires and blood samples were collected from local adult resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…previous results, which indicated that the e-waste dismantling activities had greatly increased environmental exposure of local residents (Guo et al, 2018a). The levels of individual congeners are provided in Table S4.…”
Section: Demographic Information and Exposure Levelsmentioning
confidence: 89%
See 2 more Smart Citations
“…previous results, which indicated that the e-waste dismantling activities had greatly increased environmental exposure of local residents (Guo et al, 2018a). The levels of individual congeners are provided in Table S4.…”
Section: Demographic Information and Exposure Levelsmentioning
confidence: 89%
“…The participants with no past history of critical illness were randomly selected from local residents of the two towns (n = 54 for the exposed group and n = 58 for the control group). Details of the sample chosen were presented in our previous study (Guo et al, 2018a).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giwercman et al found no association between PCB level and serum FSH and inhibin B levels in Sweden, Greenland, Poland, and Ukraine, suggesting no disturbance in the hypothalamic-pituitary-Sertoli cell axis (257). A study from China found either no significant association between serum PCB levels and reproductive hormone levels (254). Overall, evidence suggests a link between PCB exposure and disturbed hypothalamic-pituitarygonadal axis in men, particularly low serum testosterone level.…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Several studies have evaluated associations between flame retardant levels in serum or hair and reproductive hormone levels in adult men. Two studies suggested a positive association with testosterone levels (254,256). One small study suggested a negative association with inhibin B levels (255).…”
Section: Flame Retardantsmentioning
confidence: 99%